Edukasi Hukum Kesehatan Terkait Informed Consent bagi Masyarakat di Wilayah Banyumas - Teguh Setiyanta, Pentadi (LPPM Universitas Harapan Bangsa Purwokerto, 2025)
The lack of public understanding regarding legal rights in healthcare services particularly concerning informed consent remains a critical issue in various regions, including Banyumas Regency. Informed consent is a legal and ethical obligation in which patients provide voluntary agreement to medical procedures after receiving complete and adequate information. This community engagement program aimed to improve legal health literacy among local communities by providing direct education on the concept and practice of informed consent in accordance with Law No. 17 of 2023 on Health. A qualitative, participatory approach was used, involving the community at every stage of the program from socialization and training to focus group discussions and simulation-based activities. The results showed a significant increase in participants’ understanding of informed consent, along with changes in attitudes and behaviors, particularly in their willingness to assert the right to medical information. These findings suggest that community-based legal education is an effective strategy for strengthening legal awareness in healthcare. Moreover, this program fostered the emergence of local leaders who have the potential to become ongoing advocates for health law literacy within their communities.